KARAKTERISTIK MORFOLOGI BAKTERI SIMBION SPONS MENYERUPAI Cribochalina sp DARI PERAIRAN MALALAYANG SULAWESI UTARA - Gledys Giacinta Poluan; Elvy Like Ginting; Stenly Wullur; Veibe warouw; Fitje Vera Losung; Meiske Salaki (Sam Ratulangi University, 2019)
Bacteria are found to be highly associated with various marine organisms, such as sponges. Sponges are known as the product of bioactive compounds. However, some of the compounds produced by sponges are obtained by the simbion-bacteria. Therefore this situation enables sponges simbion bacteria to play a major role in producing bioactive compounds that have been isolated from the sponge. The purpose of this study is to isolate and determine the characteristics of morphology of spongy simbion bacteria resembling Cribochalina sp, which was taken from Malalayang waters, North Sulawesi. Sponge simbion bacteria grow on NB media. Initially, a free-breeding colony was being done before bacteria were accrued in the NA media by 2% sponge broth (patent SID201906301) by means of Strike Plate methods. Based on to this study we had isolate five spongy simbion bacteria that resembling the Cribochalina sp. All five of these isolations have different characteristics of morphology in terms of color, shape, size, and elevation. Keywords : bacteria, isolation, simbionts, sponges